Produção de amilase por Bacillus licheniformis utilizando meios de baixo custo - Oliveira, Daniel Paulo de (2007)
The enzymatic biotechnology industry is growing up progressively in the last decades with the utilization e production of diverse microbial enzymes. Amylases are enzymes which hydrolyze starch molecules to give diverse products including dextrin's and progressively glucose units. They play a wide field of applications. In food industries, in beer industry and others fermented drinks, in cereal for baby's food and animal feed, in paper and cellulose industry, textile industry, in detergent and cleaning products industry, in chemical and pharmaceutical industry. Screening was carrying out in solid media to amylase production in 5 strains isolated from contaminated ambient by petroleum in different temperatures (28 °C and 37 °C), respectively. The results obtained evidenced that the isolated Bacillus licheniformis UCP 1009 showed the halo formation characteristically of the 55 mm to amylase, after 72 hours of incubation. After the selection of the microorganism, fermentations was carrying out to amylase production, replacing the soluble starch, by corn starch and potato starch, trough of factorial planning 23 with 4 central's points, having a amylase's production as a answering variable, during 96 hours. The microbial growth profile was established, the pH, the glucose consumption by the DNS and determination of specific enzyme activity. The results obtained evidenced that the corn starch shown an specific activity of 0.756 U/mg, at a pH of 8.82 and a enzymatic activity of amylase 0.99 U/dL, showing a industrial potential.